Reproducibility and reliability of dental arch measurements: comparing of manual, digital, and app-based methods - Alfonso Alvarado-Lorenzo; Laura Antonio-Zancajo; Adrián Curto; Daniele Garcovich; Laura Criado-Pérez (BMC Oral Health)
Abstract Background Knowing the available dental space in a patient is crucial for orthodontists to develop a good treatment plan. Objectives To compare and evaluate the reliability, reproducibility, and accuracy of three measurement methods on models: conventional, mobile app, and digital software. Materials and methods: Maxillary and mandibular dental plaster models of 20 subjects with permanent dentition were analyzed. Three measurements were taken: manually using a digital caliper, using Nemocast 3D® software, and using the mobile app “Ruler.” These were performed by the same observer at the same initial time (T1) and repeated after 15 days (T2). Results The three methods measured each of the quadrants and each of the dental pieces similarly, with no significant differences found. Significant differences were found between the different measurement times in the manual and app ruler measurement groups. Intra-observer consistency was also observed through Pearson correlations. The measurement from the mobile app “Ruler” presented lower values compared to the other two models, especially with the measurements taken for each quadrant. Conclusion The three methods used for measuring dentoskeletal discrepancy are similar in terms of results. However, Nemocast 3D software showed greater reproducibility and reliability compared to the other two methods presenting consistency in the results measured at both time points, which may be useful for our diagnoses. Trial registration The study was conducted according to the ethical standards set by the Declaration of Helsinki for Biomedical Research and the protocol was approved by the Bioethics Committee of the University of Salamanca with number 23/1074.